2008
DOI: 10.1111/j.1600-0560.2007.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant perivascular epithelioid cell tumor (‘PEComa’): a case report and literature review of cutaneous/subcutaneous presentations

Abstract: Perivascular epithelioid cell (PEC) tumors, also called 'PEComas,' are distinct tumors showing PEC differentiation with characteristic histologic and immunophenotypic features. PEComas are rare tumors documented in the literature presenting in numerous anatomic sites including the thorax, abdomen, pelvis, soft tissue and skin. Criteria for malignancy does not exist for the subset of PEComas that pursue an aggressive clinical course. Herein, we present an unusual case of a malignant PEC tumor presenting as a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 25 publications
1
50
0
2
Order By: Relevance
“…A subset of PEComas have been reported to exhibit a malignant behaviour and pursue an aggressive clinical course [24,25]. Provisional criteria for malignany have been proposed based on worrisome features of large size ([5 cm), high nuclear grade and cellularity, necrosis and [1 mitotic figures/50 HPF [19].…”
Section: Discussionmentioning
confidence: 99%
“…A subset of PEComas have been reported to exhibit a malignant behaviour and pursue an aggressive clinical course [24,25]. Provisional criteria for malignany have been proposed based on worrisome features of large size ([5 cm), high nuclear grade and cellularity, necrosis and [1 mitotic figures/50 HPF [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other than a mass effect, no other specific signs or symptoms were noted. PEComas are rare in the head and neck [7][8][9][10][11][12][13][14][15][16][17], and those arising in the nasal cavity and larynx are even more unusual [7,12]. The common morphologic features observed in all three tumors included: large polygonal to epithelioid cells with clear or eosinophilic granular cytoplasm, centrally located nuclei with vesicular chromatin, and occasional nucleoli; a predominantly nested growth pattern associated with a delicate vascular stroma, similar to the vessels seen in clear cell renal cell carcinomas and paragangliomas; and a zone of subepithelial sparing.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our review of the English literature, we identified 13 cases [7][8][9][10][11][12][13][14][15][16][17] of primary head and neck PEComas (excluding examples described as AML). Including our three cases, this number now consists of 16 tumors (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations